Estrés laboral y su influencia en el ámbito profesional de un adulto de 41 años del Centro de Salud Nuevo San Juan - Ramirez Barzola, Joselyn Andrea (2023)
This case study revealed that work stress can affect the mental health and professional field of a 41-year-old worker at the Nuevo San Juan Health Center. It gradually emerges at the physical level and is analyzed through various assessment tools, such as medical history, clinical observations, and psychological assessment tools, such as: Beck Depression Test, Beck Anxiety Test, and the Inventory of Maslach exhaustion can help you detect specific cognitive, emotional, mental, social, and physical symptoms that are consistent with the patient's problems. In this way, Cognitive-Behavioral Therapy techniques were also used and similar techniques were used during the sessions and sent home as homework, all accompanied by a qualitative methodology and with the help of the International Classification of Diseases. The ICD-10 was able to confirm the presumed diagnosis of the patient.